International values for haemoglobin distributions in healthy pregnant women. (December 2020) - Ohuma, Eric O.; Young, Melissa F.; Martorell, Reynaldo; Ismail, Leila Cheikh; Peña-Rosas, Juan Pablo; Purwar, Manorama; Garcia-Casal, Maria Nieves; Gravett, Michael G.; de Onis, Mercedes; Wu, QingQing; Carvalho, Maria; Jaffer, Yasmin A.; et al.
Abstract: Background: Anaemia in pregnancy is a global health problem with associated morbidity and mortality. Methods: A secondary analysis of prospective, population-based study from 2009 to 2016 to generate maternal haemoglobin normative centiles in uncomplicated pregnancies in women receiving optimal antenatal care. Pregnant women were enrolled <14 weeks' gestation in the Fetal Growth Longitudinal Study (FGLS) of the INTERGROWTH-21 st Project which involved eight geographically diverse urban areas in Brazil, China, India, Italy, Kenya, Oman, United Kingdom and United States. At each 5 ± 1 weekly visit until delivery, information was collected about the pregnancy, as well as the results of blood tests taken as part of routine antenatal care that complemented the study's requirements, including haemoglobin values. Findings: A total of 3502 (81%) of 4321 women who delivered a live, singleton newborn with no visible congenital anomalies, contributed at least one haemoglobin value. Median haemoglobin concentrations ranged from 114.6 to 121.4 g/L, 94 to 103 g/L at the 3 rd centile, and from 135 to 141 g/L at the 97 th centile. The lowest values were seen between 31 and 32 weeks' gestation, representing a mean drop of 6.8 g/L compared to 14 weeks' gestation. The percentage variation in maternal haemoglobin within-site was 47% of the total variance compared to 13% between sites. Interpretation: We have generated International, gestational age-specific, smoothed centiles for maternal haemoglobin concentration compatible with better pregnancy outcomes, as well as adequate neonatal and early childhood morbidity, growth and development up to 2 years of age. Funding: Bill & Melinda Gates Foundation Grant number 49038.